A method for increasing the bandwidth of slot and patch antennas using grid‐slotted patch. Issue 2 (9th December 2020) - Xiang, Kai‐Ran; Chen, Fu‐Chang
Abstract: A method for expanding the bandwidth of slot and patch antennas is proposed in this article. The use of grid‐slotted patch helps to improve the impedance matching of the antenna, thus the bandwidth can be extended. The design process and an analysis of using a grid of slots to increase the bandwidth of a slot antenna is first given. The simulated S11 of the broadband slot antenna is less than −11 dB in the range of 2.6 to 3.42 GHz. To further demonstrate the method, an aperture‐coupled patch antenna with grid‐slotted patch is designed. The measured S11 of the broadband patch antenna is less than −10 dB in the range of 1.95 to 4.15 GHz and the peak gain is 9.6 dBi.